Perlindungan Hukum Terhadap Merek dan Indikasi Geografis Sebagai Aset Perusahaan Menurut Undang-Undang Nomor 20 Tahun 2016 - Faisal, Muhammad; AR, Azhari; Ihsan, Rachmad (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
In the era of global business competition and the knowledge-based economy, intellectual property rights (IPR) have become strategic assets that provide significant added value to companies. This paper aims to examine the role of trademarks and geographical indications (GIs) as components of intangible assets that possess both economic and legal value. A trademark functions as an identity and marketing tool that enhances product reputation and consumer loyalty, while a geographical indication protects regional products whose quality is influenced by geographic, environmental, and cultural factors. This study employs a normative legal approach using literature research methods, focusing on legislation, academic works, and relevant case studies. The findings indicate that both trademarks and geographical indications have substantial potential as corporate assets, particularly in generating economic value and strengthening competitiveness in the global market. However, their implementation and utilization in Indonesia still face several challenges, including limited awareness among business actors, weak law enforcement, and insufficient intellectual property management capacity among small and medium-sized enterprises (SMEs). Therefore, it is essential to establish synergy between business actors, the government, and society to strengthen the protection and management of intellectual property rights as part of a sustainable national economic development strategy.